The right to health in colombia: structural obstacles for its fulfillment (2000)
There is an accumulated collective frustration to guarantee the health right or all in Colombia, despite the optimistic balance about the Colombian social security reform. The historical tendency has been the fragmentation of the health delivery system according to people's payment capacity: health for poor people, health for workers, and health for wealthy people. The new system is attempting to solve this fragmentation, but the model has structural problems. Particularly, the confidence in the belief that the market will distribute the benefits in the best possible way provided that the government's regulatory mechanism and its new role will function properly. In this assay, I argue that the market only consents to a contractual right of health services, but this is not enough for reaching a broad right to health as welfare. This kind of collective option is not the result of the application of any foreign model, but the result of the process of interaction between socio-political actors. In the Colombian case, this process has been conducted in a way that favors individualistic options that sustain the current trend and raise difficulties for solving the structural obstacles that must be overcome to guarantee the right to health.